2017
DOI: 10.1002/ange.201703525
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Uranium–Iron Triple‐Bonded UFe(CO)3 and OUFe(CO)3 Complexes

Abstract: We report the preparation of UFe(CO) 3 À and OUFe(CO) 3 À complexes using alaser-vaporization supersonic ion source in the gas phase.T hese compounds were massselected and characterized by infrared photodissociation spectroscopya nd state-of-the-art quantum chemical studies. There are unprecedented triple bonds between U6d/5fa nd Fe 3d orbitals,featuring one covalent s bond and two Fe-to-U dative p bonds in both complexes.T he uranium and iron elements are found to exist in unique formal U(I or III) and Fe(ÀII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Interestingly, such a molecule was reported recently by Knecht et al and shown by state-of-the-art relativistic quantumchemical calculations to contain a quadruple bond (24). Two recent landmark experimental advances in this field are the generation of a U-Fe triple bond in the gas phase under laser vaporization by Zhou and coworkers (25) and the synthesis of a double-dative bond between Rh and U by Liddle and coworkers (26).…”
mentioning
confidence: 96%
“…Interestingly, such a molecule was reported recently by Knecht et al and shown by state-of-the-art relativistic quantumchemical calculations to contain a quadruple bond (24). Two recent landmark experimental advances in this field are the generation of a U-Fe triple bond in the gas phase under laser vaporization by Zhou and coworkers (25) and the synthesis of a double-dative bond between Rh and U by Liddle and coworkers (26).…”
mentioning
confidence: 96%
“…In 2001, the cationic species [OUFe(CO) 3 ] + was generated in the gas phase in a FTICR mass spectrometer, by reacting the uranium oxide cation UO + with Fe(CO) 5 [113]. Recently, Zhou and co-workers used a laser-vaporization supersonic ion source to produce the anions [UFe(CO) 5 ]-and [OUFe(CO) 3 ] − in the gas phase, characterized by infrared photo dissociation spectroscopy [114]. Quantum chemical studies were consistent with a uraniumiron triple bond, one covalent σ bond and two Fe-to-U dative π bonds, and a formal charge of 2-for iron.…”
Section: Uranium-transition Metal Complexesmentioning
confidence: 99%
“…28 Heterodinuclear iron oxide carbonyls, represented by OUFe(CO) 3 − , exhibit an identical chemical bonding profile to UFe(CO) 3 − . 25 So far, heterodinuclear metal oxide carbonyls simultaneously containing both main group and transition metals remain unexplored. Given the significant role of heterobinuclear oxide carbonyls in CO oxidation via the Langmuir−Hinshelwood-like mechanism, further research in this field is warranted.…”
mentioning
confidence: 99%